Risk factors for airplane headache: A multivariable logistic regression analysis in a population of career flight personnel - Prottengeier, Johannes; Kaiser, Isabelle; Moritz, Andreas; Konrad, Fabian (Cephalalgia, 2025)
Introduction: Airplane headache (AH) is a lesser-known headache disorder that occurs during and is caused by air travel. Although considered rare and current prevalence figures vary widely, it potentially affects millions annually. Risk factors for AH have not yet been adequately investigated, and so the present study aimed to identify risk factors associated with AH among a large cohort of frequent flyers. Methods: We conducted a survey using an extensive questionnaire that highlighted 30 potential risk factors for AH. We compared individuals experiencing AH with those without headaches and those with other types of headaches. Two multivariate logistic regression models were developed from risk variables and assessed using the area under the curve (AUC) of their receiver operating characteristics, with 10-fold cross-validation applied for reliability. Results: In total, 2237 questionnaires were analysed; 279 participants reported aircraft headache, while 1563 reported other forms of headache. Model selection resulted in two significant models: model 1, distinguishing AH from no headache, and model 2, differentiating AH from other headaches. Both models demonstrated promising accuracy, with AUC values of 0.794 and 0.595, respectively. Conclusions: AH notably affects productivity and workdays lost. The identified risk factors align with risk factors for headache in general, as well as headache at high altitudes. Interestingly, folic acid supplementation could have a positive, protective effect. Further research is warranted to explore these relationships and potential preventive strategies.
CRIS-Team Scopus Importer:2025-05-09
Keywords: airplane headache; headache attributed to airplane travel; headache attributed to disorder of homeostasis; international classification of headache disorders; multivariable logistic regression analysis; risk factors